Effect of Addition of Basil Leaf Extract (Ocinum Basilicum) in Egg Yolk Diluent on the Quality of Liquid Semen of Landrace X Duroc Cross Pigs - Elsaday Imanuel Widu; Agustinus R. Riwu; Setyani Ni Made Paramita (Jurnal Global Ilmiah, 2026)
This study aims to test the use of basil leaf extract (BLE) levels in citrate- egg yolk (C-EY) diluent to maintain landrace x duroc crossbred broas spermatozoa during preservation. This study used fresh semen from a 1.5-year-old landrace and duroc crossbred boar in healthy condition and trained in semen collection. This study was designed using a completely randomized design consisting of six treatments and five replications, namely: T0 = C-EY, T1: C-EY + 2% BLE, T2: C-EY + 4% BLE,T3: C-EY + 6% BLE, T4: : C-EY + 8% BLE, T5: : C-EY + 10% BLE. The variables tested included: motility, viability, abnormality, and survival rate (SR) of spermatozoa. The diluted semen was stored in a styrofoam box at a temperature of 15-200C. The collected data were analyzed using Analysis of Variance and continued with Duncan's test. The results showed that the P2 treatment at the 48th observation hour produced spermatozoa quality with a significant difference in value (P<0.05) compared to other treatments with motility values: 57.00±0.54%, viability: 66.50±3.88%, abnormality: 5.70±1.04%, and SR spermatozoa: 56.28 hours. It can be concluded that the addition of basil leaf extract at a level of 4.0% in citrate- egg yolk diluent provides a good response in maintaining the quality of duroc pig spermatozoa for up to 56.28 hours of storage.